2019
DOI: 10.3390/brainsci9080188
|View full text |Cite
|
Sign up to set email alerts
|

The Scanpaths of Subjects with Developmental Prosopagnosia during a Face Memory Task

Abstract: The scanpaths of healthy subjects show biases towards the upper face, the eyes and the center of the face, which suggests that their fixations are guided by a feature hierarchy towards the regions most informative for face identification. However, subjects with developmental prosopagnosia have a lifelong impairment in face processing. Whether this is reflected in the loss of normal face-scanning strategies is not known. The goal of this study was to determine if subjects with developmental prosopagnosia showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This led the authors to speculate that prosopagnosia may be characterized by both impaired face perception from damage to the right fusiform face network, as well as inability to attend to facial regions useful for identification, such as the eyes, which may be mediated by the left frontal network. Indeed, other studies of acquired prosopagnosia have found a failure to process eye information, particularly under attentionally demanding conditions (Pancaroglu et al, 2016;Caldara et al, 2005), whereas some but not all studies of developmental prosopagnosia have shown reduced scanning of the eyes (Lee, Corrow, Pancaroglu, & Barton, 2019;Bobak, Parris, Gregory, Bennetts, & Bate, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This led the authors to speculate that prosopagnosia may be characterized by both impaired face perception from damage to the right fusiform face network, as well as inability to attend to facial regions useful for identification, such as the eyes, which may be mediated by the left frontal network. Indeed, other studies of acquired prosopagnosia have found a failure to process eye information, particularly under attentionally demanding conditions (Pancaroglu et al, 2016;Caldara et al, 2005), whereas some but not all studies of developmental prosopagnosia have shown reduced scanning of the eyes (Lee, Corrow, Pancaroglu, & Barton, 2019;Bobak, Parris, Gregory, Bennetts, & Bate, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This was also found in another study examining the ability of DPs and controls to detect changes in “critical” features and “non-critical” features, where DPs showed similar patterns of response to controls [ 32 ]. One study which used eye tracking to measure scan paths during a face memory task showed no difference in scan paths of faces in DPs and controls, with both groups showing a bias towards the eyes over the mouth [ 52 ] (for different findings, see [ 31 ]). Taken together with our results, this suggests that DPs may be impaired in detecting changes to all internal facial features rather than having a specific or pronounced deficit for the eye region.…”
Section: Discussionmentioning
confidence: 99%
“…Remedial strategies aim to train more general skills that can be applied to any face, with the idea to facilitate more effective "normal" processing strategies. Typically, these techniques are used in patients with prosopagnosia due to impaired non-perceptual mechanisms that would be difficult to achieve otherwise (Young & Ellis, 1989) games or tasks to establish correct face scanning paths (Lee et al, 2019). Internal feature training focuses on the ability to distinguish different facial features, such as lip shape, eye colour, or distances between facial features, such as the spacing between the eyes and brows or the nose and mouth (DeGutis et al, 2007;Ding & Martinez, 2010).…”
Section: Approaches In Remedial Rehabilitation Of Prosopagnosiamentioning
confidence: 99%